Student Activity in Local Area Network (LAN) Installation - Siska, Jumiati (International Journal of Multi Discipline Science (IJ-MDS), 2024)
The purpose of this study is to determine the implementation of the Direct Instruction learning model to students’ activeness in Local Area Network (LAN) installations in class X TKJ of SMKN 2 Central Bengkulu. The method used in this research was the descriptive qualitative method. Research on the implementation of the direct instruction learning model to students’ activeness in class X TKJ of SMKN 2 Central Bengkulu, totalling 25 students. Data collection techniques used were observation, interview, and documentation. The data analysis technique in this research uses interviews and direct observations that can be combined. The results showed the implementation of the direct instruction learning model to students’ activeness in Local Area Network (LAN) installations is implemented by researchers in well-structured stages. Includes orientation, presentation, structured practice, and independent practice. Students’ activeness in the learning process went well and active participation was seen when the researcher applied the direct instruction learning model, as evidenced by the observation sheet of students’ activeness from the 12 elements in the 4 assessment indicators that had been filled in by observers with the results obtained namely that 9 element indicators were 75% while for the other 3 indicator elements it is 25%.